6x+2=2(2x+2)

Simple and best practice solution for 6x+2=2(2x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+2=2(2x+2) equation:


Simplifying
6x + 2 = 2(2x + 2)

Reorder the terms:
2 + 6x = 2(2x + 2)

Reorder the terms:
2 + 6x = 2(2 + 2x)
2 + 6x = (2 * 2 + 2x * 2)
2 + 6x = (4 + 4x)

Solving
2 + 6x = 4 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
2 + 6x + -4x = 4 + 4x + -4x

Combine like terms: 6x + -4x = 2x
2 + 2x = 4 + 4x + -4x

Combine like terms: 4x + -4x = 0
2 + 2x = 4 + 0
2 + 2x = 4

Add '-2' to each side of the equation.
2 + -2 + 2x = 4 + -2

Combine like terms: 2 + -2 = 0
0 + 2x = 4 + -2
2x = 4 + -2

Combine like terms: 4 + -2 = 2
2x = 2

Divide each side by '2'.
x = 1

Simplifying
x = 1

See similar equations:

| -7(3k-7)=196 | | -9(8x-35)=-477 | | 368=r+8(5+5r) | | -2y+6x=12 | | 6w-2=28 | | 8-5(3+8a)=-327 | | 2[a-5]=14 | | 3=9-2c | | 3tg^4x-10tg^2x+3=0 | | 4x+32-2x+16=2 | | 12[3+a]=48 | | 7-6(8x+2)=-293 | | y+11=5y+29 | | 0.5(3x-1)+0.5x=2x-0.5 | | 12[x+11]=156 | | x-0.1=0.9 | | 4.8x-8.6=20.2 | | 5(4b+3)=135 | | (12)=-3x+10 | | 1485=-11(9x+9) | | 14x-8x=42 | | -15=.5[x+6] | | 5(5p+4)+4(3p+2)= | | 2n+25=4n+23 | | 190/50 | | 7w+2w=45 | | y-10=-x+2 | | x-3.6=1.4 | | 5k-4=2k+11 | | -5+8k=7k+4-7 | | Ab/c=xy/z | | 3x(2xy)(-3x^5y^2)= |

Equations solver categories